Safety Level of Microorganism-Bearing Products Applied in Soil-Plant Systems - Vassileva, Maria; Mocali, Stefano; Canfora, Loredana; Malusá, Eligio; García del Moral, Luis F.; Martos, Vanessa; Flor-Peregrin, Elena; Vassilev, Nikolay (Frontiers in Plant Science, 2022)
The indiscriminate use of chemical fertilizers adversely affected ecological health and soil microbiota provoking loss of soil fertility and greater pathogen and pest presence in soil- plant systems, which affect the quality of food and human health. Therefore, the sustainability, circular economy, environmental safety of agricultural production, and health concerns made possible the practical realization of eco-friendly biotechnological approaches like biofertilizers, biopesticides, and reuse of agro-industrial wastes applying novel and traditional methods and processes. However, the advancement in this field of the Biotechnology/Agriculture is related to the safety of the microbially-based products. While the existing regulations are well-known and followed in the preparation and application of waste organic matter and microbial inoculants, more attention should be paid to gene transfer, antibiotic resistance, contamination of the workers and environment in farms and plants, and microbiome changes. These risks should be carefully assessed, and new analytical tools and regulations should be applied to ensure safe and high-quality food.